A Devonian >2000-km-long dolerite dyke swarm-belt and associated basalts along the Urals-Novozemelian fold-belt: part of an East-European (Baltica) LIP tracing the Tuzo Superswell. (2nd January 2016) - Puchkov, Victor; Ernst, Richard E.; Hamilton, Michael A.; Söderlund, Ulf; Sergeeva, Nina
Abstract: Two dolerite dyke swarms are recognized along and paralleling the Ural Mountains, Russia. The Uralian swarm is 1400-km long (2300-km long if traced from its inferred plume centre). Further north, the Pay-Khoy swarm can be traced through the Pay-Khoy–Novaya Zemlya fold belt for a distance of c. 250 km (800-km long if traced from its inferred plume centre). An Upper Devonian age for volcanism associated with the Pay-Khoy swarm is well constrained by isotopic data. A Devonian age for the Uralian swarm was until now supported mainly by broad geological field relationships between the dykes and host rocks, i.e. dykes locally cut Proterozoic, Ordovician to Devonian sedimentary rocks, but never Carboniferous sequences. Rare isotopic age determinations also support an Upper Devonian age for the weakly altered dykes. Herein, a new precise U–Pb baddeleyite age determination of 377.2 ± 0.9 Ma is reported from a large (>50-m wide) gabbro–dolerite dyke cutting the uppermost Proterozoic in the Middle Urals. This result confirms a predicted Upper Devonian age for the dyke and gives additional support to the Devonian age of the Uralian swarm. Given this precise U–Pb age, the Uralian swarm is correlated with the Pay-Khoy swarm, Devonian basalts which are widely distributed across the East European (Baltica) Craton, as well as alkaline magmatic rocks and kimberlites of more restricted distribution. Collectively, this Devonian magmatism can be combined into a Kola–Dnieper Large Igneous Province (LIP) with two proposed mantle plume centres: (1) a southern centre at the intersection of the Dnieper-Donets aulacogen and Uralian swarm and (2) a northern centre in the Barents Sea, at the convergence between the Pay-Khoy dyke swarm and an unnamed swarm extending from the northern coast of the Kola Peninsula, as well as converging rift/graben zones. Furthermore, this Kola–Dnieper LIP of the East European (Baltica) Craton, with its two plume centres, is approximately coeval with the Yakutsk–Vilyui LIP and its plume centre on the eastern side of the Siberian Craton. These two LIPs were in close proximity at that time and their three plumes may represent a superplume derived from an active part of a single deep mantle LLSVP (Large Low Shear Wave Velocity Province), the so-called Tuzo superswell.